Smart alert for smart transportation - Kishore Kumar, K; Sravan Kumar, Atmakuri; Amarnadh Gupta, Sunkari; Venkata Naga Parvesh, Sure (International Journal of Engineering and Technology, 2018)
Road accident is mostly happened to a road user, though they happen quite often. The most unfortunate thing is that we don't learn from our mistakes on road. Most of the road users are quite well aware of the general rules and safety measures while using roads but it is only the laxity on part of road users, which cause accidents and crashes. Main cause of accidents and crashes are due to human errors. Many of the road accidents occurs in the human errors by overriding, drink and drive and don’t follow safety precautions on roads. Various national and international researchers have found these as most common behavior of Road drivers, which leads to accidents [4].So, we came up with an application to alert hospital emergency and cops. all the users can easily handle this application when accident emergency occur. In the same way we can save life of a person by occur road accident.